Chemical Components of Contact Lens Solutions - Lum, V J; Lyle, W M (Canadian Journal of Optometry, 1981)
With the myriad of contact lens solutions on the market today, it becomes difficult to choose the appropriate contact lens system for the patient. Three major factors to be considered in the choice are safety, efficacy and cost. To determine the efficacy of a solution, an understanding of its components is required. Unfortunately, certain manufacturers are unwilling to disclose their formulations. The authors encourage practitioners not to use such solutions. Most manufacturers, however, do list the active ingredients.